PEMANFAATAN LEAFLET DAN POSTER SEBAGAI MEDIA EDUKASI GIZI SEIMBANG TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP REMAJA PUTRI DI ACEH BESAR - Al Rahmad, Agus Hendra; Sofyan, Hizir; Usman, Said; Mudatsir, Mudatsir; Binti Firdaus, Shausan (Media Penelitian dan Pengembangan Kesehatan, 2023)
Aceh is one of the provinces in Indonesia where around 5-10% of teenagers aged 13-15 years are underweight or very thin, and 8.3% are obese. Understanding balanced nutrition is very important for teenagers so there is a need for education regarding this matter. Balanced nutrition education is effective when delivered through the right media. This study aimed to determine the effect and effectiveness of balanced nutrition education using leaflets and poster media on the knowledge and attitudes of adolescent girls. Quantitative research using a Quasy experiment design. The research location was in Senior High School 1, Ingin Jaya Aceh Besar, in 2023. A sample of 66 schoolgirls was divided into two intervention groups: balanced nutrition education using leaflet and poster media. Data were collected using a questionnaire. Direct intervention was carried out for five days with balanced nutrition material, totaling two credits. Data analysis was performed using the Dependent T-test and Independent T-test statistical tests at 95% CI. Results, there is an effect of balanced nutrition education using leaflet media in improving knowledge and attitudes (p<0.05). Likewise, balanced nutrition education using poster media showed a significant effect (p<0.05). However, there was no difference between the use of leaflets and poster media in improving the knowledge and attitudes of adolescent girls towards balanced nutrition (p>0.05). In conclusion, balanced nutrition education using leaflet and poster media has an effect in improving knowledge and attitudes, but there was no difference in effectiveness in providing education about balanced nutrition.